Natural Occurrence of Ochratoxin A in Blood and Milk Samples from Jennies and Their Foals after Delivery - Vincenzo Lippolis (Toxins, 2020)
An assessment of the natural ochratoxin A (OTA) exposure of seven Martina Franca jennies was carried out by analyzing blood and milk samples collected close to and after delivery. A total of 41 and 34 blood samples were collected from jennies and foals, respectively, and analyzed by ELISA. A total of 33 milk samples were collected from jennies and analyzed by the HPLC/FLD method based on IAC clean-up. Furthermore, 53 feed samples were collected from January to September and analyzed by a reference method (AOAC Official Method No. 2000.03) for OTA content. Feed samples showed OTA levels up to 2.7 ng/g with an incidence of 32%, while the OTA incidence rate in jennies’ blood samples was 73%, with a median value of 97 ng/L and concentrations ranging from <LOD to 6000 ng/L. A seasonal effect on OTA levels in positive blood samples was observed, with increases in the 53% of the positive ones from April to June. Concerning foals, the incidence rate of blood samples was 50%, with a median value of 52 ng/L, and concentrations ranged from <LOD to 4034 ng/L. The incidence of milk samples was 36%, with levels ranging from <LOD to 82 ng/L. In conclusion, the results showed a natural exposure of jennies and foals to OTA, and its presence in jenny milk could pose a risk for human newborns, considering its well-known nutritional and health properties.